The Transformational Leadership in a Public Educational Institution - Martínez Contreras, Ysrael Alberto (2014)
The transformational leadership allows managers influence their teachers who recognize and attributed control to the director. The research investigated what are the characteristics of the transformational leadership of the director of a public educational institution of the UGEL 07. Through the study we recognized the features of transformational leadership in the director. The research identified three elements of the transformational leadership attributed to the director. The views expressed by the teachers and the data obtained from the respondents in order to obtain a description of the exercise of transformational leadership in the selected institution were also examined.